2020
DOI: 10.33308/26674874.2020342200
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi ve Sınıf Öğretmenliği Lisans Programlarının Çocuğun Bütünsel Gelişimi Açısından Değerlendirilmesi

Abstract: Gelişimsel olarak aynı dönemde bulunan ve örtüşen yaş gruplarındaki çocuklara öğretmenlik yapan okul öncesi ve sınıf öğretmenlerinin ortak mesleki temel yeterlikler ile birlikte birbirini tamamlayan mesleki donanımlara sahip olmaları beklenir. Bu çalışma, erken çocukluk dönemi çocukları ile çalışacak olan okul öncesi ve sınıf öğretmeni adaylarının, çocukların farklılıklardan doğan potansiyellerini fark edip ihtiyaçlarını karşılayabilmeye yönelik muhtemel yeterliklerini, 2018-2019 öğretim yılında uygulamaya kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…One of the teacher training undergraduate curricula revised in 2018 was the class teaching curricula. Research in the literature revealed problems experienced with the revised class teaching curricula (Kamışlı et al, 2020;Kılıç-Özmen, 2019;Ulubey and Başaran, 2019). This research identified that the 2018 class teaching undergraduate curricula reduced hours for some lessons, removed applied hours in some lessons, removed some basic education lessons from the curricula or converted them to elective lessons and added new lessons to the class teaching undergraduate curricula compared to the previous 2007 curricula.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
“…One of the teacher training undergraduate curricula revised in 2018 was the class teaching curricula. Research in the literature revealed problems experienced with the revised class teaching curricula (Kamışlı et al, 2020;Kılıç-Özmen, 2019;Ulubey and Başaran, 2019). This research identified that the 2018 class teaching undergraduate curricula reduced hours for some lessons, removed applied hours in some lessons, removed some basic education lessons from the curricula or converted them to elective lessons and added new lessons to the class teaching undergraduate curricula compared to the previous 2007 curricula.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%